SUSTAINABLE CONSTRUCTION: GREEN BUILDING PRACTICES FOR GREEN INFRASTRUCTURE - Budi Santoso (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to examine the implementation of green building practices in the framework of sustainable construction in infrastructure projects in Indonesia. Using a descriptive qualitative approach, data was collected through in-depth interviews, field observations, and document studies on several projects that have applied green building principles. The results show that the application of principles such as energy efficiency, water conservation, and the use of environmentally friendly materials has begun to be carried out, albeit with varying levels of application. Green buildings are proven to provide long-term economic and environmental benefits, including energy savings and reduced carbon emissions. However, challenges are still faced, such as a lack of understanding of industry players, limited experts, and uneven supporting policies. This study recommends strengthening policies, sustainable education, and the use of technology and regulatory incentives to accelerate the adoption of green buildings. The results of this study make an important contribution in encouraging the transformation of the construction sector towards a more sustainable and environmentally friendly direction.